Dynamic thermal performance of ultra-light and thermal-insulative aerogel foamed concrete for building energy efficiency. (1st July 2020) - Zhang, Haiying; Yang, Jianming; Wu, Huijun; Fu, Ping; Liu, Yanchen; Yang, Wenbing
Highlights: A new type of high-performance aerogel foamed concrete was prepared. The delay time of aerogel foamed concrete is twice of polystyrene or concrete. The heat loss of aerogel foamed concrete was 1/3 of concrete. Abstract: A new type of high-performance aerogel foamed concrete was prepared by using aerogel powder as filling material and chopped glass fiber as reinforcement. By using the aerogel foamed concrete and the other materials (viz. ordinary concrete and EPS) as the insulation, an insulted box was carried out on the thermal performance under a constant outside temperature of 35℃ and initial inside temperature of 25℃. The results indicate that when inside temperature increased to 90% of the stable 35℃, the required time for the aerogel foamed concrete was prolonged to 9 h compared to 5 and 4.5 h for EPS and ordinary concrete. Meanwhile, a 3R2C heat transfer model was established for the insulated box, whose calculated results agreed well with the experimental. By using the model, the predicted time lag of the aerogel foamed concrete insulation box is twice as long as that of the EPS or ordinary concrete box. The heat loss in 48 h of the aerogel foamed insulating concrete box was 59.79 J, approximately 1/3 of that from the ordinary concrete box. The results indicate that the aerogel foamed concrete has better thermal insulating performance from solar radiation or extremely hot weather for applications in low and zero energy buildings.